Thermal preference of adult males of Cryphiops caementarius previously acclimated at different temperatures - Reyes-Avalos, Walter (2020)
In this work, we establish the thermal preference of Cryphiops caementarius adult males, previously acclimated at different temperatures. Shrimp were collected from the Pativilca River. In the laboratory, shrimp were acclimated for 30 days in nine aquariums, each with 10 circular containers. In each container, there was a shrimp (10 per aquarium). Acclimation temperatures were 19, 24 and 28 °C. The gradient temperature system (12 to 33 °C) consisted for a PVC gutter (3 m long and 10 cm deep) with 18 compartments. Submersible thermoregulators (100W) were placed at one end of the gutter and the other end, frozen hydrogel bags. The thermal preference was determined by the acute method and the tests were performed between 08:00 and 14:00 h. Shrimp acclimated at 24 °C moved to compartments whose temperatures were higher than the acclimation temperature. Shrimp acclimated at 24 °C moved to compartments whose temperatures were around the acclimation temperature. Shrimp acclimated at 28 °C moved to compartments where temperatures were lower than acclimation. The thermal preference of acclimated shrimp at 19 °C was 22.7 °C, and those acclimated at 24 °C were 24.8 °C, both without significant differences (p>0.05). On the other hand, in acclimated ones at 28 °C it was 21.1 °C, which only differed (p<0.05) with those acclimated at 19 °C. The final thermal preference was 24.5 °C.